What do we know about developing patient portals? a systematic literature review. (2nd September 2015) - Otte-Trojel, Terese; de Bont, Antoinette; Rundall, Thomas G; van de Klundert, Joris
Abstract: Objective Numerous articles have reported on the development of patient portals, including development problems and solutions. We review these articles to inform future patient portal development efforts and to provide a summary of the evidence base that can guide future research. Materials and Methods We performed a systematic review of relevant literature to answer 5 questions: (1) What categories of problems related to patient portal development have been defined? (2) What causal factors have been identified by problem analysis and diagnosis? (3) What solutions have been proposed to ameliorate these causal factors? (4) Which proposed solutions have been implemented and in which organizational contexts? (5) Have implemented solutions been evaluated and what learning has been generated? Through searches on PubMed, ScienceDirect and LISTA, we included 109 articles. Results We identified 5 main problem categories: achieving patient engagement, provider engagement, appropriate data governance, security and interoperability, and a sustainable business model. Further, we identified key factors contributing to these problems as well as solutions proposed to ameliorate them. While about half (45) of the 109 articles proposed solutions, fewer than half of these solutions (18) were implemented, and even fewer (5) were evaluated to generate learning about their effects. Discussion Few studies systematically report on the patient portal development processes. As a result, the review does not provide an evidence base for portal development. Conclusion Our findings support a set of recommendations for advancement of the evidence base: future research should build on existing evidence, draw on principles from design sciences conveyed in the problem-solving cycle, and seek to produce evidence within various different organizational contexts.